Biophysical and life-history determinants of hydraulic lift in Neotropical savanna trees - Scholz, Fabian Gustavo (2008)
1. Ecological and physiological characteristics of vascular plants may facilitate or constrain hydraulic lift. Studies of hydraulic lift typically include only one or few species, but in species-rich ecosystems a larger number of representative species needs to be studied. 2. Measurements of sap flow in tap roots, lateral roots and stems, as well as stable isotope labelling techniques were used to determine the occurrence and relative magnitude of hydraulic lift in several individuals of nine co-occurring Brazilian savanna (Cerrado) tree species differing in life-history traits, and to assess physical and biological determinants of this process at the tree and ecosystem level. 3. The occurrence of reverse sap flow observed in deciduous and brevideciduous species during the dry season was consistent with hydraulic lift. The evergreen species did not exhibit reverse flow. Consistent with their ability to carry out hydraulic lift, the brevideciduous and deciduous species had both shallow and tap roots (dimorphic root systems), whereas the evergreen species had mostly deep roots (monomorphic root systems). 4. In the deciduous and brevideciduous species, the contribution of tap roots to transpiration increased substantially as the dry season progressed. Seasonal changes in the contribution of tap roots to transpiration were not observed in the evergreen species. 5. There was an inverse relationship between rates of reverse sap flow and seasonal loss of hydraulic conductivity in lateral roots, suggesting that hydraulic lift in Cerrado woody plants may help maintain the functionality of the lateral roots in exploring dry and nutrient rich superficial soil layers without directly enhancing the amount of water uptake. 6. Reverse sap flow in lateral roots of the deciduous and brevideciduous species increased asymptotically as the driving force for water movement from roots to the soil increased. This nonlinear relationship implies that additional sinks for water such as nocturnal transpiration and refilling of internal water storage tissues may compete for internal water resources during the dry season. 7. There appears to be a trade-off between greater year-round access to nutrients in the upper soil layers (deciduous and brevideciduous species) and a greater access to deep and more reliable water sources during the dry season (evergreen species), which has implications for whole-ecosystem water, carbon and nutrient balance in Neotropical savannas. © 2008 The Authors.